Code-Mixing as a Promotion Strategy in Shopping Centres - Novia Sophia Sophia (Universitas Muhammadiyah Mataram, 2018)
The aim of this study is to investigate the goals of Code-Switching and Code-Mixing and how it is used in a communicative strategy among the stand banners in Lombok Epicentrum Mall (LEM). Data were collected by documenting with pictures of stand banners at several outlets in LEM. The method used in analyzing the data is qualitative in approach by identifying, classifying, describing and explaining the code-switching and the code mixing data in the corpus and how they have been used to promote the products sold at the stores. The result shows that the purposes of using Code-Switching and Code-Mixing as a communication strategy in their promotion and it also shows that code mixing is more dominant than code switching. The advertisers mix-match the languages that they use with English and Bahasa Indonesia because they assume that these practices are the right ones and matching Indonesian words into English makes it sound cooler instead of using Bahasa Indonesia. This indicates that English signifies a high culture and class status while Indonesian is inferior in status. In fact, being commonly used in numerous stand banners for a long period of time, the mixing use of Indonesian and English as well as matching the sounds in the languages have been very common and accepted in Indonesian discourse practices. Therefore, the implication that they communicate their business strategy of promotion their products by using CS and CM is to inform and attract the customers that they are in a higher level or class, thus, it acquires them to communicate or promoted like so.